1974
DOI: 10.2307/1142540
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Discretion in Determining the Severity of Punishment for Incarcerated Offenders

Abstract: Many studies have been conducted on the decision-making processes of social control agencies. These studies have provided considerable insight into both the legal and non-legal factors which affect people who come into contact with representatives of such agencies. While substantial research has already been conducted concerning the discretionary practices of police, prosecutors, judges and juries and the effect of their practices on the legal norm-violator's contact with the law, there is one area in the crim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Past research findings showed significant relationships between age, education, marital status, and socioeconomic status of the inmate and parole decisions. Younger, married offenders and those with more schooling and employment prior to incarceration were more likely to be granted parole (Scott, 1974). Results tended to be ambiguous regarding race and parole release.…”
Section: Offender-related Variablesmentioning
confidence: 91%
See 4 more Smart Citations
“…Past research findings showed significant relationships between age, education, marital status, and socioeconomic status of the inmate and parole decisions. Younger, married offenders and those with more schooling and employment prior to incarceration were more likely to be granted parole (Scott, 1974). Results tended to be ambiguous regarding race and parole release.…”
Section: Offender-related Variablesmentioning
confidence: 91%
“…These studies examined how variables such as seriousness of the offense, time served and the number of total felonies committed, and previous paroles impacted parole decisions. Scott (1974) found that seriousness of the offense was a major factor that resulted in parole denial and extensive stays in prison. He noted that parole board members were only willing to release an inmate after they believed that the inmate suffered commensurately for the crime (Scott, 1974, p. 217).…”
Section: Offense-related Variablesmentioning
confidence: 99%
See 3 more Smart Citations